1998
DOI: 10.1002/(sici)1097-0223(199803)18:3<255::aid-pd255>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

First 10 000 chorionic villus samplings performed on singleton pregnancies by a single operator

Abstract: Chorionic villus sampling (CVS) was performed in 10 000 consecutive singleton pregnancies by a single principal operator, working in two institutions. The procedure was performed between 8 and 32 gestational weeks: transabdominal (TA) sampling was carried out in 8479 cases and transcervical (TC) in 1521. Patients were referred for chromosomal risk in 89·1 per cent of cases, Mendelian disorders in 10·5 per cent, and DNA investigations for paternity or infectious agents in 0·4 per cent of cases. The sampling suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 40 publications
2
0
0
1
Order By: Relevance
“…Another study in a Turkish population focused on the same issue and revealed a CA rate of 4.4% ( 12 ) . The medical literature reports culture media failure lower than 1.0% ( 11 , 13 , 14 , 15 ) and we observed approximately the same rate (1.2%). The patients and their spouses accepted the second attempt in only 7 of 27 cases (6 CVS and one AC) and a new AC was performed, all of which revealed a normal karyotype.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another study in a Turkish population focused on the same issue and revealed a CA rate of 4.4% ( 12 ) . The medical literature reports culture media failure lower than 1.0% ( 11 , 13 , 14 , 15 ) and we observed approximately the same rate (1.2%). The patients and their spouses accepted the second attempt in only 7 of 27 cases (6 CVS and one AC) and a new AC was performed, all of which revealed a normal karyotype.…”
Section: Discussionsupporting
confidence: 81%
“…The rates of other indications were also compatible with the literature ( 8 , 9 ) . Our study demonstrated a CA rate up to 7% (154/2185) ( 7 , 10 , 11 ) . Another study in a Turkish population focused on the same issue and revealed a CA rate of 4.4% ( 12 ) .…”
Section: Discussionsupporting
confidence: 52%
“…Diese Daten decken sich annähernd mit den Ergebnissen einer australischen Multizenterstudie (1,2 % Abortusrate) [11] sowie den Angaben von Brambati et al [12], der 10 000 Chorionzottenbiopsien, die von einem einzigen Operateur vorgenommen wurden, retrospektiv aufgearbeitet hat (Abortusrate 1,2 -3,8 %).…”
Section: Ergebnisseunclassified